The appropriateness of the prescribed police uniform for women in the service - Gaviola, Lovely Anne T.; Elumba, Patricia Santos (2001.)
The study focused on the appropriateness of the prescribed police uniform for female PNP, specifically the GOA-A (General Office Attire type A). The researcher attempted to asses the profile of acceptance of GOA-A, the female PNP's reactions on the uniform and identified details that they wished to change. The survey was conducted within Central Police District. Sixty (60) Commissioned and Non-Commissioned Police Officers from Camp Karingal and the different Police Stations all over Quezon City were given and Likert / checklist type questionnaire to solicit their assessment about their present prescribed uniforms. Interview with the respondents were also conducted which served as added information for this research. The result of the survey-questionnaire showed that the uniform in terms of the fabric is appropriate for daily use of the female police because because of its colorfastness to laundering and its wash and wear ability. A greater percentage showed their satisfaction on the aesthetic and functional aspect of the uniform. majority of them wished not to change any of the details cited in the questionnaire. It was only in the group of senior female PNP who preferred a lighter shade for their uniforms. On comfort performance, there were more respondents who feel itchy and warm when wearing the uniform. From the result of the personal interview, it was evident that most of the female PNP prefer to use pants despite the prohibition of the PNP. There were also good number of the female PNP, especially those who have been in the service for more than five years, who do not comply with the details on the specifications given by PNP for their uniforms. They made alterations to suit their preferences. This came about with the laxity of the PNP in implementing the prescribed uniform. Aside from the conflict in the results, there were also a good number of respondents who gave neutral answers to the specific questions in the questionnaire. The researcher considered these people as those who had their uniforms altered or those who were just afraid to give opinions because of the political instability in the PNP brought about by the change in leadership.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Women's clothing